Long-term prognostic significance of HER2-low and HER2-zero in node-negative breast cancer. (September 2022) - Almstedt, Katrin; Heimes, Anne-Sophie; Kappenberg, Franziska; Battista, Marco J.; Lehr, Hans-Anton; Krajnak, Slavomir; Lebrecht, Antje; Gehrmann, Mathias; Stewen, Kathrin; Brenner, Walburgis; Weikel, Wolfgang; Rahnenführer, Jörg; et al.
Abstract: Background: Recently, novel antibody––drug conjugates (ADCs) showed clinical activity in a subset of advanced human epidermal growth factor receptor 2 (HER2)-negative patients. We investigated the prognostic significance of HER2-low and HER2-zero tumours. Patients and methods: The retrospective cohort study included 410 consecutive node-negative breast cancer patients without adjuvant systemic therapy treated between 1985 and 2000 (median follow-up: 16.73 [IQR 8.58–23.45] years). 351 (85.6%) were HER-2 negative and subdivided into HER2-zero (immunohistochemistry [IHC] score 0) and HER2-low (IHC score 1+ or 2+/in situ hybridisation [ISH]-negative). HER2 gene expression was available in 170 (48.4%) patients. Differences in HER2 status for immunohistochemistry, gene expression and clinico-pathologic parameters were assessed using Fisher's exact test, Pearson's correlation and Mann–Whitney test. Prognosis was investigated using the Kaplan–Meier method and Cox regression analyses. Results: Of the 351 HER2-negative patients, 198 (56.4%) had HER2-low tumours and 153 (43.6%) were HER2-zero. Significant differences between HER2-zero and HER2-low tumours were found in histologic grading (P = 0.001), Ki-67 (P = 0.013) and HER2 gene expression (P = 0.002). HER2-low patients had significantly longer disease-free survival (DFS) (15-year rate: 67.5% [95% CI 61.0–74.7] vs. 47.3% [95% CI 39.9–56.1], P < 0.001) and overall survival (OS) (15-year rate: 75.4% [95% CI 69.4–81.9] vs. 66.8% [95% CI 59.5–74.9], P = 0.009). The OS difference was observed in hormone receptor (HR)-positive (P = 0.039) but not HR-negative (P = 0.086) tumours. The results of multivariable analyses confirmed the independent prognostic significance of HER2 status (DFS: HR, 0.546; 95% CI, 0.402–0.743; P < 0.001; OS: HR, 0.653; 95% CI, 0.458–0.932; P = 0.019). Conclusion: HER2-low patients had a better survival than HER2-zero patients. Highlights: Prognosis was assessed in patients with HER2-low and HER2-zero early breast cancer. Patients with HER2-low breast cancer had a significantly better prognosis. HER2-low patients had longer disease-free survival and overall survival. Immunohistochemical HER2 subdivision was confirmed by gene expression analysis.